Prevalence of Narcotics-Induced Poisoning in Children under 18 Years of Age Referring to the Al-e-Jalil Educational and Therapeutic Center, Aq Qala, Golestan Province (2020-2022) - Mohsen Yekrang; Mahsa Besharat; Sima Besharat; Javad Enayat; Khadije Amjadi (مجله دانشگاه علوم پزشکی گرگان)
Background and Objective: Poisoning is one of the most common reasons for emergency department visits worldwide. Awareness of poisoning patterns helps identify risk factors and enables early diagnosis. In Iran, narcotics are among the main causes of poisoning in children. The current study aimed to determine the prevalence of narcotics-induced poisoning in children under 18 years old referring to the Al-e-Jalil Educational and Therapeutic Center in Aq Qala, Golestan Province. Methods: This retrospective descriptive study was conducted on 36 children aged 1 month to 18 years (22 boys and 14 girls; mean age: 51.62±36.25 months) referring to the Al-e-Jalil Educational and Therapeutic Center in Aq Qala due to narcotics-induced poisoning from 2020 to 2022. Samples were included in the study using census. Patients’ medical records were reviewed and recorded in a checklist. Results: The highest poisoning rate stemmed from the consumption of opium (69.4%), followed by methadone (25%). Decreased level of consciousness upon hospital admission was determined to be 66.7%. The interval between poisoning and hospital admission was 5.60±3.86 hours. The mean length of hospital stay was 1.25±0.80 days, and no patients died. Most children were male (61.1%), Turkmen (69.4%), and rural residents (86.1%). The highest cases of poisoning occurred in the summer (36.1%). The most common route of contact was oral (97.2%). Conclusion: The poisoning rate with opium is higher compared to other narcotics. However, there is strong evidence of increased opium use among young people and some evidence of increased methadone use.